RANCANG BANGUN APLIKASI SISTEM INFORMASI CARWASH & AUTOCARE BERBASIS ANDROID PADA MAHKOTA MOTOR JAYA MAKMUR - Jefry Fernando; Ika Ratna Indra Astutik; Hamzah Setiawan (Jurnal Teknoinfo, 2023)
Mahkota Motor Jaya Makmur Carwash & Autocare is located in Cangkringmalang, Kec. Beji, Pasuruan, East Java is one of the places for vehicle carwash and autocare services for vehicle needs whose role is to help solve problems experienced by damage to the user's vehicle. In carrying out daily community activities, vehicle users do not have time to wash and perform maintenance on the vehicle, the services at Mahkota Motor Jaya Makmur Carwash & Autocare are expected to help users, the service in this place has a function to provide comfort , satisfaction or a sense of security for each customer because the process in car washing using Hydraulic (lifting the car) is used so that the bottom of the car is easy to clean. One way to develop a business from this place is to create an Android-Based Carwash and Autocare Information System application, to provide more convenience for users to choose services in the application. This application was successfully built with the JavaScript programming language as an android application builder. The React Native framework is used to display a selection of services available in the app and various information about these places.